2022
DOI: 10.1016/j.jcct.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of 4D cardiac computed tomography feature tracking myocardial strain and comparison against speckle-tracking echocardiography in patients with severe aortic stenosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
(42 reference statements)
2
14
0
Order By: Relevance
“…Furthermore, it has recently been demonstrated that CT can also be applied for strain measurements. LA strain measured by CT correlates strongly with strain measurements derived from speckle-tracking echocardiography (94)(95)(96).…”
Section: Cardiac Computed Tomography Cardiac Computed Tomographymentioning
confidence: 66%
“…Furthermore, it has recently been demonstrated that CT can also be applied for strain measurements. LA strain measured by CT correlates strongly with strain measurements derived from speckle-tracking echocardiography (94)(95)(96).…”
Section: Cardiac Computed Tomography Cardiac Computed Tomographymentioning
confidence: 66%
“…CMR does not only allow to accurately assess LV dimension/function and tissue characteristics, but also proved to inherit important information from RV function. Echocardiography represents a reproducible method to derive RV GLS and RVEF but may be challenging in patients with impaired echo window [ 38 ], and RV GLS values only moderately agree to those of CMR, underlining the need for separate cut-off values [ 24 , 39 ]. CMR-based evaluation of the updated Lake-Louise Criteria [ 40 ] and endomyocardial biopsy are currently the cornerstones in the diagnosis of myocarditis, also incorporating powerful outcome prognosticators from LV function and tissue characteristics [ 9 , 11 13 , 19 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CT, when scanned throughout a full cardiac cycle (ie, 4-dimensional CT), allows assessing cardiac volume and function, as well as myocardial strain calculations, which correlates well with echocardiography. 15 The potential of 4-dimensional CT in tailoring risks and predicting outcomes, such as reverse remodeling and mortality following a transcatheter aortic valve replacement, has been assessed in a study by our group including 608 patients. CT-based LV mass index and left ventricular ejection fraction could predict 12-month reverse remodeling, whereas CT-based LVEF and left atrial ejection fraction emerged as independent predictors of survival.…”
Section: See Article By Patel Et Almentioning
confidence: 99%
“…It, therefore, seems that routine 4-dimensional CT in severe AS can provide high diagnostic performance in the detection of concomitant ATTR-CM. 18 However, these measurements were only evaluated in a global fashion, and combining the approaches of regional function with ECV CT would definitely both, further enhance our understanding of the disease mechanism, and refine risk stratification.…”
mentioning
confidence: 99%